2018
DOI: 10.3329/bjms.v17i1.35286
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cucurbita extract effect on changes of AGEs, lipid and glycemic profile and CRP in type 1 diabetic rats

Abstract: Background: Clinically, diabetes is an important risk factor or a range of diseases including nephropathy,retinopathy, angiopathy and deficiency and it is increasing in prevalence according to some estimates. (Cucurbita pepo L.) from the cucurbitaceae family has a low calorie but high nutritional and medical value. The aim of this study was to observe the effect of cucurbita extract on serum factors of STZ induced diabetic rats including glucose level AGEs, lipid profile (cholesterol, HDL, LDL, and TG) and CRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Abuelgassim and Al-Showayman [ 50 ] studied the effect of pumpkin seed supplementation in diet on serum glucose level in atherogenic rats and found nonsignificant data of blood glucose level in atherogenic rats and rats fed with pumpkin seeds diet. Results supporting our study were present when Sayahi and Shirali [ 51 ] studied the effect of pumpkin ( Cucurbita pepo ) fruit extract on serum glucose concentrations and found a significant decrease in blood glucose level in diabetic groups treated with pumpkin fruit extract.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Abuelgassim and Al-Showayman [ 50 ] studied the effect of pumpkin seed supplementation in diet on serum glucose level in atherogenic rats and found nonsignificant data of blood glucose level in atherogenic rats and rats fed with pumpkin seeds diet. Results supporting our study were present when Sayahi and Shirali [ 51 ] studied the effect of pumpkin ( Cucurbita pepo ) fruit extract on serum glucose concentrations and found a significant decrease in blood glucose level in diabetic groups treated with pumpkin fruit extract.…”
Section: Resultssupporting
confidence: 90%
“…Mohamed et al [ 60 ] studied the effect of substituting pumpkin seed protein isolate at 25, 50, 75, and 100% level with casein on serum lipid levels in CCl 4 -intoxicated rats and found supporting results. Sayahi and Shirali [ 51 ] studied the effect of pumpkin ( Cucurbita pepo ) fruit extract on serum lipid concentrations, and contradictory results for TG and TC were obtained with a nonsignificant increase in TG as in diabetic group, TG were 92.40 mg/dl, and in group treated with pumpkin extract, TG were 93.16 mg/dl, and a significant increase in TC as in diabetic group TC was 66.60 mg/dl, and it was increased to 73.83 mg/dl in diabetic group treated with pumpkin fruit extract. Results for LDL-C and HDL-C were similar to our study as an increase in HDL-C was observed (diabetic rats' group: 34.28 mg/dl and pumpkin extract-treated group: 38.76 mg/dl), and decrease in LDL-C was observed (diabetic rats' group: 14.60 mg/dl and pumpkin extract-treated group: 13.16 mg/dl).…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus (DM) has increased the prevalence in the world, especially in developing countries 1,2 . The prevalence numbers in patients with diabetes mellitus were growing rapidly in the world that might generally correlated lead as with living in the urban area, increasing older adult population, and lifestyle alteration 3 . Diabetes is a metabolic disease characterized by hyperglycemia and impaired carbohydrate metabolism, fat, and insulin resistance, and it becomes one of the causes of death in the world 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the effect of dietsupplementation with the extract of C. pepo leaves on lipid profile of rats was studied to observe for hypolipidemic potential. Previous works in the area have paid mind to the hypolipidemic potential of the fruits and seeds [11][12][13]. Hence, this work is novel in the sense that it pays attention to the leaves, which hitherto, had received very little attention.…”
Section: Introductionmentioning
confidence: 99%